2013
DOI: 10.1103/physreve.87.025001
|View full text |Cite
|
Sign up to set email alerts
|

Effective rheology of bubbles moving in a capillary tube

Abstract: The ALICE Collaboration has measured inclusive J/ψ production in pp collisions at a center of mass energy √ s = 2.76 TeV at the LHC. The results presented in this Letter refer to the rapidity ranges |y| < 0.9 and 2.5 < y < 4 and have been obtained by measuring the electron and muon pair decay channels, respectively. The integrated luminosities for the two channels are L e int = 1.1 nb −1 and L µ int = 19.9 nb −1 , and the corresponding signal statistics are N e + e − J/ψ = 59 ± 14 and N= 1364 ± 53. We present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 32 publications
3
61
0
Order By: Relevance
“…The system characterized by ensemble distribution in equation (7) is by construction ergodic [46]. The time average of a function g = g(x b ) is g, and we have…”
Section: A the One-dimensional Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The system characterized by ensemble distribution in equation (7) is by construction ergodic [46]. The time average of a function g = g(x b ) is g, and we have…”
Section: A the One-dimensional Distributionmentioning
confidence: 99%
“…Working towards the goal to determine the ensemble distribution beyond one dimension, we start with conclusions from a one-dimensional sequence of links [46]. We have reported earlier that the probability that a bubble has a certain position x b,ij in the link, is inversely proportional to the velocity dx b /dt of the fluid in that link…”
Section: A the One-dimensional Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason behind the discrepancy between the results of Rassi et al and those of Sinha et al is the possibility of a non-zero threshold pressure that observed in the later study, under which there would be no flow, which was assumed to be zero in the former study. The reciprocals in the brackets are provided in order to compare the exponent values reported in the literature [14-17] with those we present here in this article, as we express our results as Q as a power law in ∆P , whereas the cited papers write ∆P as a power law in Q .This power law behavior is in contrast to the assumption of linearity in the relation between flow rate and pressure drop that is generally assumed in the relative permeability approach dominating reservoir simulations [18].For a single capillary tube with varying diameter, Sinha et al [19] showed that the average volumetric flow rate q in the steady state has a non-linear squareroot type relationship with the pressure drop ∆P as q ∼ ∆P 2 − P 2 c . This was shown analytically by integrating the instantaneous linear two-phase flow equation over the whole capillary tube.…”
mentioning
confidence: 83%